2008
DOI: 10.1103/physrevb.77.184103
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of Fe-doped Ni-Mn-Ga ferromagnetic shape-memory alloys

Abstract: We have studied the effect of Fe addition on the structural and magnetic transitions in the magnetic shape memory alloy Ni-Mn-Ga by substituting systematically each atomic species by Fe. Calorimetric and AC susceptibility measurements have been carried out in order to study the magnetic and structural transformation properties. We find that the addition of Fe modifies the structural and magnetic transformation temperatures. Magnetic transition temperatures are displaced to higher values when Fe is substituted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…In the case of Fe and Co substituted alloys the entropy changes for a given value of e/a are lower than those in the corresponding ternary Ni-Mn-Ga system. This drop confirms the suggested strengthening of magnetic exchange coupling when adding Fe and Co which results in a decrease of the free energy difference between the parent and martensite phases when the alloy orders magnetically [34], and therefore stabilization of the high temperature phase. The reduction of entropy change at a given electron concentration is considerably larger in Co-doped alloys which means that Co has a stronger effect on magnetic exchange coupling than Fe.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the case of Fe and Co substituted alloys the entropy changes for a given value of e/a are lower than those in the corresponding ternary Ni-Mn-Ga system. This drop confirms the suggested strengthening of magnetic exchange coupling when adding Fe and Co which results in a decrease of the free energy difference between the parent and martensite phases when the alloy orders magnetically [34], and therefore stabilization of the high temperature phase. The reduction of entropy change at a given electron concentration is considerably larger in Co-doped alloys which means that Co has a stronger effect on magnetic exchange coupling than Fe.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, we showed that selective partial substitution of 3d elements in Ni-Mn-Ga alloys is a useful tool to study the role of electron concentration on the structural and magnetic phase transitions exhibited by these materials. Specifically, we studied the effect of Fe addition on the Curie, premartensitic and martensitic transitions and we determined a detailed phase diagram of quaternary Ni-Mn-Ga-Fe alloys for low Fe concentrations [34]. Previously, the study of doping in Ni-Mn-Ga alloys had been focused only on its effect on the martensitic and the ferromagnetic phase transitions [35][36][37][38][39][40][41][42][43][44][45][46].…”
mentioning
confidence: 99%
“…Moreover, the Curie temperature of the martensite phase (T C,M ) is slightly higher or almost equal to the Curie temperature of the parent phase (T C,P ), and the ΔM in the vicinity of martensitic transformation temperature (T M s ) is very small. Similar phase diagrams can be found for Ni-Mn-Ga systems such as in Ni 2+x Mn 1−x Ga [30][31][32] and other sections [33,34] [36], Ni-Mn-Ga-Cu [37][38][39], and Ni-Mn-Ga-Fe [40,41] systems also show similar behaviors, and a magnetically coupled structural transition, i.e., a direct transition from region I to region IV, can be found in a wide range of compositions.…”
Section: Introductionsupporting
confidence: 53%
“…The TP values found for cooling and heating are also the same. Soto et al [42] studied Fe-doped NiMnGa (Ni52.5−xMn23Ga24.5Fex) alloys, finding that the premartensitic transition temperature was 186 K for the x = 4.4 alloy. No significant thermal hysteresis was detected at the premartensitic transition, and no appreciable features were observed in the calorimetric curves at the premartensitic transition.…”
Section: Resultsmentioning
confidence: 99%